Reflecting the Nepali Social Forum processes and 2018 event. Issue 2 (17th February 2020) - Pyakurel, Uddhab Pd.
ABSTRACT: This article reflects on one experiment that grounds the politics of World Social Forum in national and regional struggles. Nepal has now built a dynamic but fragile democratic process after a decade long Maoist insurgency that led to political transformation including secularism, republicanism, etc. The analysis is particularly relevant for political movements seeking ways forward in a political situation marked by sectarian struggles but also by the need to bring unity in the struggle against externally induced forces of oppression and exploitation.